Mobile e-detection of Banyuwangi’s citrus fruit maturity using k-nearest neighbor - Chairul Anam; Solehatin Solehatin (Universitas Ahmad Dahlan, 2020)
Banyuwangi is the largest oranges-producing city in East Java, and the orange produced is Siamese citrus fruit. Siamese is Banyuwangi local citrus fruit often found at the harvest time and has a sweet taste. To determine the citrus fruit level, people can detect it from the color and texture. In this modern era, people can use an application to determine the citrus fruits' maturity level. From the elements of color and texture, this research will add the citrus fruit's contours, namely the pore size of the citrus fruit and the distance between the curve of the tip of the orange. Taking pictures of citrus fruits will be following the application stages that will be used as the image of inputting the data. The detection is then conducted using the K-NN method based on several criteria based on the input image after the feature extraction process. The feature extraction stages are segmentation, normalization, thresholding, and thinning, which will be produced in several criteria: the maximum RGB value, the minimum RGB value, pore size, and the distance between the tip's curve of the orange. The research results that have been carried out are based on the research stages to get a similarity percentage following the inputted data. The E-Detection application can provide information to citrus farmers, especially beginner citrus farmers, to know the level of fruit maturity oranges to be harvested.